EDUKASI KESEHATAN DIRI DAN LINGKUNGAN MASYARAKAT DUYU - Tandah, Muhamad Rinaldhi; Jamaluddin; Salingkat, Syarif Permana; Khusnul Diana (Jurusan Farmasi FMIPA Universitas Tadulako, 2024)
Personal and environmental health are crucial factors in improving the quality of life within a community. In Duyu, there remains a lack of awareness regarding the importance of maintaining personal and environmental hygiene. Therefore, comprehensive education is needed to enhance public knowledge and awareness of the significance of personal and environmental health. The aim of this initiative is to increase public understanding of the importance of personal and environmental health, to teach proper hygiene practices, and to encourage the community to adopt a healthy lifestyle and maintain a clean environment. The activities were divided into several stages: health education and awareness sessions (covering the importance of personal hygiene, proper handwashing techniques, food and beverage hygiene, environmental cleanliness, waste management, the importance of good sanitation, exercise, healthy eating, and adequate rest), practical demonstrations (on proper handwashing steps, waste separation between organic and non-organic materials, and simple composting techniques), and participatory activities (such as collective efforts to clean the surrounding environment from waste and sources of disease, and the dissemination of health and hygiene information in strategic locations). The normality test revealed that the pre- and post-test data were not normally distributed, thus a non-parametric test was conducted. The Wilcoxon test resulted in an Asymp Sig. (2-tailed) value of 0.000 (less than 0.05), indicating that the educational intervention on personal and environmental health significantly impacted the participants' knowledge and behaviors.